Reviewing the RCM on Cooling Water Pump of LNG Production Company - Shaneza Fatma Rahmadhanty; Trika Pitana; Nurhadi Siswantoro (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2019)
Maintenance is one of the important things to maintain a company in the industry. A company, such as LNG production company, must be able to produce and meet energy needs independently to support all operations, such as cooling water system that functions to control the temperature and pressure so that the production process runs optimally. If this system is disrupted, there will be excess use of water, waste water, and energy costs needed which result in higher total operational costs. With good and right care, it can reduce all risks posed. One component that plays a role in the cooling water system is a pump. This pump serves to flow the cooling water which is seawater to the LNG industry plant. At present, the amount of Work Order data recorded from the problems obtained from the pump requires maintenance updates. In this study, the method in the maintenance programs are used based on the Reliability-Centered Maintenance (RCM) implementation. RCM will increase cost efficiency, reliability, pump uptime, and propose maintenance tasks. Beside pump, the reviewing also involve supports components that affect pump optimization. In this paper, the functions, causes, and effects are identified and the new scheduled maintenance tasks are shown.